Trial of labour after caesarean (TOLAC) is associated with increased risk for instrumental delivery. (2nd January 2017) - Inbar, Rotem; Mazaaki, Shali; Kalter, Anat; Gat, Itai; Sivan, Eyal; Schiff, Eyal; Hendler, Israel
Abstract: We compared the rates of instrumental delivery in a cohort of nulliparous women at term ( n  = 19, 416), to primiparous women who attempted labour after prior caesarean (TOLAC) ( n  = 1747). The rate of instrumental deliveries was higher in the TOLAC group compared to nulliparous gravidas (17.3 vs. 15% respectively, p  = 0.001). The difference was more prominent for women who eventually had successful vaginal delivery (TOLAC: 23.9% vs. controls: 17.1%, p  < 0.0001 respectively). Based on our results, previous caesarean whether urgent or elective was associated with an increased risk of instrumental delivery in the subsequent pregnancy.